Microwave AC Resonance Induced Phase Change in Sb2Te3Nanowires - Tse, Pok Lam; Tian, Fugu; Mugica-Sanchez, Laura; Rueger, Oliver; Undisz, Andreas; Mothrath, George; Ronning, Carsten; Takahashi, Susumu; Lu, Jia Grace (Nano Letters, 2020)
Scaling information bits to ever smaller dimensions is a dominant drive for information technology (IT). Nanostructured phase change material emerges as a key player in the current green-IT endeavor with low power consumption, functional modularity, and promising scalability. In this work, we present the demonstration of microwave AC voltage induced phase change phenomenon at ∼3 GHz in single Sb2Te3 nanowires. The resistance change by a total of 6-7 orders of magnitude is evidenced by a transition from the crystalline metallic to the amorphous semiconducting phase, which is cross-examined by temperature dependent transport measurement and high-resolution electron microscopy analysis. This discovery could potentially tailor multistate information bit encoding and electrical addressability along a single nanowire, rendering technology advancement for neuro-inspired computing devices.
CRIS-Team Scopus Importer:2023-04-20
Keywords: AC voltage; nanowire; phase change material; transport measurement